Enhancing medical students' point-of-care ultrasound confidence and competence - Peticca Benjamin; Sandberg Alex; Korus Jacob; Kolansky Matthew A.; Zhao Huaqing; Magee Mark; Gibbons Ryan C. (Journal of Ultrasonography)
Undergraduate medical education in point-of-care ultrasound remains limited. Common barriers to implementation include limited curricular space, financial constraints, and lack of instructors. This pilot study aims to assess the efficacy of a one-day symposium on medical students' point-of-care ultrasound skills, knowledge, and confidence.